ASSESSMENT OF HEALTH AND QUALITY OF LIFE: VARIATIONS BETWEEN NATURAL AND INDUCED MENOPAUSAL WOMEN - AXANAYA RAJESH; MEGHA THAMPY (The Journal of Research ANGRAU, 2025)
Menopausal health impacts among women vary. The research aimed to examine the problems of women with natural menopause and induced menopause in the year 2022-23.The evaluation of the study was on the basis of a self-prepared questionnaire and Menopause-Specific Quality of Life developed by Department of Family and Community Medicine, Sunnybrook Health Science Centre, University of Toronto, Canada in 1996 (MENQOL),the tool to evaluate the quality of life. About fifty sample each in natural menopause and induced menopause were chosen from  various places in Kerala.The study opined that either the induced and natural menopause women  had no significant relation with BMI. But the waist hip ratio pointed out that 20 per cent induced  menopause women were at higher risk category than natural menopausal women (4%). Also, the  physiological problems like diabetes (70%), dizziness (62%) and gastritis (60%), psychological problems like mood swings (100%), anxiety (66%), trouble sleeping (64%), sexual and genital problems like decreased libido (84%), itching (72%), vaginal dryness (60%) were high among induced menopausal women than natural menopause women. Menopause specific quality of life questionnaire showed that the quality of life at physical (flatulence-90%, aching in muscles and joints- 96%) and sexual domains (change in sexual desire-90%) affected mostly among induced menopause women.